Communications '98 : proceedings of the National Conference on Communications, Indian Institute of Science, Bangalore, January 29-31, 1998 - National Conference on Communications Bangalore, India (1998; Hari, K. V. S; Mukherji, Utpal (New Delhi: Tata Mc-Graw-Hill Pub. Co., 1998)
With reference to India
Includes bibliographical references and index
Keywords: Signal processing; Communication